2019
DOI: 10.1038/s41467-019-10977-5
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Variation of a major facilitator superfamily gene contributes to differential cadmium accumulation between rice subspecies

Abstract: The original version of this Article did not acknowledge Jianyin Xie as an equally contributing author with a superscript 6. Also, there was an error in the second sentence of the Abstract, which incorrectly read 'While several transport systems have been reported, the complicity of rice Cd transport and accumulation indicates the necessity of identifying additional genes, especially those that are responsible for Cd accumulation divergence between indica and japonica rice subspecies.' The correct version stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The carryover effect of these shifts into the soil microbial populations is an ongoing area of research (Fernández-Baca et al, 2021b). Genetic approaches are also used to decrease root to shoot translocation of Cd (Ueno et al, 2009;Yan et al, 2019), and to identify genes associated with uptake of multiple essential elements in different growth conditions (Zhang et al, 2014;Liu et al, 2021), locations (Norton et al, 2014), and varieties (Pinson et al, 2015).…”
Section: Complementary Rice Breeding Research Effortsmentioning
confidence: 99%
“…The carryover effect of these shifts into the soil microbial populations is an ongoing area of research (Fernández-Baca et al, 2021b). Genetic approaches are also used to decrease root to shoot translocation of Cd (Ueno et al, 2009;Yan et al, 2019), and to identify genes associated with uptake of multiple essential elements in different growth conditions (Zhang et al, 2014;Liu et al, 2021), locations (Norton et al, 2014), and varieties (Pinson et al, 2015).…”
Section: Complementary Rice Breeding Research Effortsmentioning
confidence: 99%
“…The indica rice variety transporting the japonica allele OsCd1 V449 , which is involved in root Cd uptake, can decrease Cd concentrations in grains . The rice restorer line YaHui2816 was screened to exhibit steadily less Cd content from 146 rice lines in the field and pot experiments, which could be used for LA rice breeding . Field experiment of 39 maize cultivars revealed that selection of LA cultivars was an efficient approach to reduce the Cd concentrations in maize grains .…”
Section: Introductionmentioning
confidence: 99%
“…90 MicroRNA166 modulates Cd tolerance and accumulation in rice through the regulation of its target gene, homeodomain containing protein 4 (OsHB4). 91 Gao et al (2019) reported that Zma-miR393b and Zma-miR167f are response to the Cd stress. 92 Strategies To Alleviate Cd Accumulation.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, heavy accumulation of Cd in the edible parts threatens human health (Yan et al 2019). It has been con rmed that daily exposure to 30-50 mg Cd greatly increases the risk of diseases, such as cancer, renal dysfunction, and hypertension (McLaughlin et al 1999;Ebbs et al1997).…”
Section: Introductionmentioning
confidence: 99%